The Barron's mathematics study dictionary - Tapson, Frank; Atkins, Robert A.; Tapson, Frank (Hauppauge, NY : Barron's Educational Series, 1998)
Includes alphabetically arranged terms of the basic vocabulary of mathematics along with definitions for each.
Adaptation of: The Oxford mathematics study dictionary.
Includes index.
Keywords: Mathematics -- Dictionaries, Juvenile; Mathematics -- Dictionaries